Salmon Patch and Mongolian Spot Frequency in the Northwest of Iran: A Descriptive Study - Mohammad Hassan Karegar Maher; Seifollah Heidar Abady; Aydin Tabrizi (Mashhad University of Medical Sciences, 2016)
Background: Cutaneous manifestations are commonly observed in the neonatal period. It is important to differentiate physiologic skin lesions from pathologic ones to avoid parents' concerns. Regarding this, the current study aimed to investigate the frequency and localization of salmon patch (SP) and Mongolian spot (MS) in Iranian newborns to assess the potential relationship between the neonatal and maternal characteristics. Methods: This descriptive cross-sectional study was conducted on one thousand healthy infants born at Al-Zahra University Hospital in the northwest of Iran during August-September 2014. For the aims of the study, the neonates were examined by a pediatrician. The collected data included gender, gestational age, anatomical sites of the lesions (MS and SP), birth weight of the newborns, parental consanguinity, parity, and maternal age. The exclusion criteria included major known congenital chromosomal or metabolic abnormalities, stillbirths, and admission in the Sick Newborn Care Unit or Neonatal Intensive Care Unit. Results: According to the results of this study, the frequency rates of MS and SP among 1000 newborns were found to be 32.3% and 14.5%, respectively. Maternal age was the only variable which showed a statistically significant relationship with SP (P=0.024). In addition, sacral region and upper eyelid were found to be the most common site of MS and SP involvement, respectively. Conclusion: MS and SP which are commonly observed in the routine neonatal examination may worry parents regardless of their association with an underlying systemic disorder. Regarding this, we recommend careful examination of the newborns' skin by pediatrician in the neonatal wards.